Analisis Implementasi Standar Akuntansi Pemerintah Berbasis Akrual Pada Rumah Sakit Umum Daerah Wangaya - Sri Mahayuni, Ni Putu (Hita Akuntansi dan Keuangan, 2023)
Government Regulation (PP) No. 71 of 2010 concerning Full Accrual-Based Government Accounting Standards (SAP) which is used as a substitute for the previous regulation, PP No. 24 of 2005 which is temporary. To realize the implementation of PP 71 of 2010 is not an easy thing, efforts and preparations are needed starting from increasing resource capabilities, adequate infrastructure, technology and information systems related to the application of accrual-based SAP. The aim of this research is to examine how the Government Accounting Standards based on accrual are put into practice at Wangaya Regional Hospital. The approach used in conducting this research is qualitative with a descriptive method. The implementation model used by George Edward III policy implementation model which prioritizes 4 aspects, namely Communication, Resources, Disposition and Bureaucratic Structure.This research was conducted using interview techniques using interview guidelines in the form of points of questions regarding Accrual-Based SAP Implementation. The results of this study show that Wangaya Hospital, judging from Edward III’s theory, has applied SAP.